Factors Associated with Gender Differences in Incidence of Burn among Patients Older than 59 Years of Age - Mahmood Moosazadeh; Motahareh Kheradmand; Maryam Entezari (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Risk of burn is influenced by some factors including life conditions, lifestyle, and culture. Factors such as reduced physical strength, damaged protection mechanisms, taking various drugs leave elderly at more risk of burns. The aim of this study was to determine the factors associated with gender differences in incidence of burn in patients older than 59 years of age admitted to Sari Zare Hospital. Materials and methods: This cross-sectional study was done in patients older than 59 years of age who were admitted in Sari Zare Hosptal , a referral center for three provinces (Mazandaran, Golestan, Semnan), between 2013 and 2015. Participants were selected using census method. Data was collected using the patient's documents and a checklist for recording the information. Independent t test, Chi-square and Fisher's exact test were used in order to analyze the data. Results: A total of 169 patients was admitted in hospital including 85 males (50.3%). The mean age of patients was 70.4 ± 8.2. In urban areas the frequency of burns was higher in men than that in women (62.1% vs. 38.1%), while in rural areas this frequency was higher among women (68.2% vs 37.9%). We found a significant relationship between gender and place of residence, educational level, cause of burn, location of burn, and age group (P<0.05). Conclusion: Our findings showed that incidence of burn is different in elderly men and women in terms of place of residence, education level, cause of burn, location of the burn, and age. Therefore, appropriate planning and prevention interventions are required.